1998
DOI: 10.1038/sj.sc.3100540
|View full text |Cite
|
Sign up to set email alerts
|

Aging and life adjustment after spinal cord injury

Abstract: Study Design: A ®eld study of aging after spinal cord injury (SCI) was conducted by surveying the life adjustment of a large sample of participants with SCI. Objectives: The purpose of the current study was to compare life adjustment scores between cohorts of participants based on chronologic age, age at injury onset, time since injury and percentage of life with SCI. Summary of Background Data: Existing cross-sectional research suggests that age is negatively correlated and time since injury is positively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…24 Possibly, such difficulties could be counterbalanced by processes of adjustment strengthened by age and experience, as confirmed by the improvement of QoL or by the decrease of depressive symptoms over time, which are well documented in SCI studies. 13,14 If we consider time since injury, our data supports the hypothesis that a longer duration of SCI is significantly associated with a higher prevalence of task-oriented coping strategies, confirming the increasing relevance of such adaptive strategies over time. Further research, and especially longitudinal studies, should be conducted in line to increase our knowledge of these important aspects.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…24 Possibly, such difficulties could be counterbalanced by processes of adjustment strengthened by age and experience, as confirmed by the improvement of QoL or by the decrease of depressive symptoms over time, which are well documented in SCI studies. 13,14 If we consider time since injury, our data supports the hypothesis that a longer duration of SCI is significantly associated with a higher prevalence of task-oriented coping strategies, confirming the increasing relevance of such adaptive strategies over time. Further research, and especially longitudinal studies, should be conducted in line to increase our knowledge of these important aspects.…”
Section: Discussionsupporting
confidence: 73%
“…This process, especially for people with SCI, helps them to face the constraints of the physical condition without forgoing an active role in their families and in society. 13 The role of coping strategies can also be seen from this developmental point of view. Our finding that emotion-oriented coping negatively correlated with various dimensions of QoL confirms the assumption that these kinds of strategies, despite being normative and to some extent helpful in the acute phase of SCI, can be dysfunctional in the long run.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 The impact of aging on SWB suggests that persons who were older at injury onset and chronologically older had lower levels of SWB and lower self-reported adjustment. 35,43 White participants reported higher SWB across several indices, and males had lower scores than women on satisfaction interpersonal relations. 44 The trajectory of employment satisfaction contradicts somewhat the patterns seen in other life satisfaction areas.…”
Section: Natural Course Of Scimentioning
confidence: 99%
“…Adjustment after SCI has been shown to have di erent e ects associated with age and time since injury. 14,18,19 Pain and fatigue have been associated with age; economic stability and number of symptoms reported were associated with time since injury; and economic stability and perceived health were associated with an interaction between age and time since injury. 10 A general study of health status and SCI showed that outcomes were more associated with age than with time since injury.…”
Section: Introductionmentioning
confidence: 99%